Peran Rapma FM sebagai Radio Komunitas Kampus Universitas Muhammadiyah Surakarta - Ramadan, Eno Prasetyo; , Drs.Budi Santoso, S. Sos, M.,Si (2017)
A community radio is a kind of media which is less popular but it can still be found with various purposes. Rapma FM, one of community radio in Surakarta under the authority of Universitas Muhammadiyah Surakarta, starts to show its role as the media of information, entertainment, education, and can influence the students of UMS. This research aimed to see the role of Rapma FM as community radio in UMS. The researchapplied a qualitative escriptive method involving community radio of Rapma FM as the object of study. Data were collected used interview, documentation, and observation. The results of this study showed the role of Rapma FM as information medium through several programs like Sudut Kampus, 11N1, News Flash, KhasanahPetang and others. Information was given related to the needs of students. The entertainment part in Rapma FM was shown through the song played in this radio with various genres. Rapma FM played its role as education medium through the education of sciences, technology, and Islam. Finally, Rapma FM influenced students through its programs and also public service advertisements.